Comparison of Sensitivity, Specificity, and Accuracy of ISS, RTS, and TRISS Instruments in Predicting Mortality of Trauma Patients - Fenny Tianda; Kumboyono Kumboyono; Suryanto Suryanto (Jurnal Health Sains, 2024)
This study aims to compare the effectiveness of three trauma scoring systems—Injury Severity Score (ISS), Revised Trauma Score (RTS), and Trauma and Injury Severity Score (TRISS)—in predicting mortality among trauma patients at Inche Abdoel Moeis Regional General Hospital Samarinda's emergency room. Trauma assessment tools are crucial for reducing mortality rates and enhancing patient outcomes. While ISS focuses on anatomical factors, RTS integrates physiological parameters, and TRISS combines both for a comprehensive evaluation. Previous research suggests their effectiveness in mortality prediction, albeit with variations in performance. The absence of a dedicated trauma assessment system at the hospital underscores the urgency of this research. By evaluating the performance of ISS, RTS, and TRISS, this study aims to inform clinical practice and enhance trauma patient management, ultimately reducing mortality rates and improving outcomes in the emergency room setting. The study's methodology involves retrospective analysis of trauma patient data, including demographics, injury characteristics, and outcomes. Statistical analysis will compare the performance of the three scoring systems in predicting mortality with implications for trauma care protocols and resource allocation. Results will contribute to evidence-based decision-making in emergency room settings, facilitating more accurate triage and treatment strategies for trauma patients.